Associations between cognitive functions and apoliprotein E Ɛ4 genotype: Systemic review - Sapranavičiūtė, Laura; Tamošiūnas, Abdonas (Psichologija, 2012)
Deterioration of cognitive functions is becoming a more and more important issue in the context of aging. So there is a growing interest in studies looking for the risk factors of deterioration of cognitive functions. Apolipoprotein E is a plasma protein whose major function is lipids transportation. APOE ɛ4 allele of the Apolipoprotein E gene is known as a risk factor of Alzheimer disease. Previous researchers stated, that APOE ɛ4 also might be related to cognitive performance in normal aging. However, results of previous studies are quit confusing: different studies established various associations between APOE ɛ4 and specific cognitive functions. Moreover, longitudinal studies failed to establish prognostic value of APOE ɛ4 genotype to different levels of cognitive functions deterioration. So the purpose of this study is to review prospective, observational, cohort studies that had researched the association between APOE ɛ4 and cognitive functions using a systematic analysis method.The weight of evidence suggests that APOE ɛ4 is associated with cognitive functions in healthy adults. APOE ɛ4 carriers are likely to have a lower level of cognitive functions. Associations between specific cognitive functions and APOE ɛ4 genotype are quite confusing. The most consistent finding was a negative relationship between APOE ɛ4 genotype and performance of memory and executive functioning. The presence of APOE ɛ4 and attention test results were less likely to be associated. Reasoning and verbal abilities were mostly not connected to APOE ɛ4 genotype. Associations between APOE ɛ4 and cognitive function differ in the groups of healthy adults, adults with mild cognitive impairment or Alzheimer disease. There were established that APOE ɛ4 is associated with cognitive functions in a cognitively impaired population. People with mild cognitive impairment or Alzheimer disease more often tended to be APOE ɛ4 carriers in comparison with people who are not cognitively impaired. Longitudinal studies revealed different links between APOE ɛ4 and cognitive functions. Although APOE ɛ4 might be a risk factor of deterioration of cognitive functions in healthy and impaired cognitive functions groups. Yet prognostic value of APOE ɛ4 in deterioration of cognitive functions in Alzheimer population is confusing. The current review suggests that APOE ɛ4 has an effect on cognitive functions. It might be a risk factor for the deterioration of cognitive functions in healthy adults and cognitively impaired population. However further researches are needed to establish specific associations between APOE ɛ4 genotype and different cognitive functions in healthy adults and disease populations.
Keywords: cognitive functions; APOE ɛ4 genotype